Histopathological analysis of the synovium in trapeziometacarpal osteoarthritis. (December 2019) - Rein, Susanne; Okogbaa, Janet; Hagert, Elisabet; Manthey, Suzanne; Ladd, Amy
Dorsoradial and anterior oblique ligaments were harvested during surgery in 13 patients with symptomatic trapeziometacarpal osteoarthritis, which had been graded preoperatively by a modified Eaton-Littler radiographic grading. Ligaments, including the periligamentous synovium, were stained with S100 protein, neurotrophic receptor p75, protein gene product 9.5, calcitonin gene related peptide, acetylcholine, substance P, neuropeptide Y, noradrenaline, N-methyl-D-aspartate-receptor and Met/Leu-enkephalin. The synovium was classified as showing no, low-grade or high-grade synovitis. Free nerve endings had higher immunoreactivity for substance P than for N-methyl-D-aspartate-receptor, enkephalin and noradrenaline. The synovial stroma had less immunoreactivity for N-methyl-D-aspartate-receptor than for noradrenaline, substance P and calcitonin gene related peptide. There was no relation between the grade of osteoarthritis and the visual pain analogue scale, synovitis score, immunoreactivity of all antibodies and quantity of free nerve endings or blood vessels. Synovium in trapeziometacarpal joint osteoarthritis produces several neuromediators causing a polymodal neurogenic inflammation and which may serve as biomarkers for osteoarthritis or therapeutic targets.